Involvement of prostaglandins in the pathophysiology of endometriosis - Meresman, Gabriela Fabiana (2012)
Prostaglandins are bioactive lipids that possess multiple and diverse functions. In reproductive biology, they are involved in the regulation of ovulation, in endometrial physiology and in the process of menstruation. Furthermore, cyclooxygenases (COX) levels, which are key enzymes for the synthesis of prostaglandins, have been found to be elevated in pathologic, tumoral and inflammatory processes. In endometriosis, prostaglandins are not only implicated in pain, but they are also critical for the establishment as well as for the development of the disease. The high levels of prostaglandin E2 (PGE2) found in the peritoneal fluid from patients with endometriosis, not only favor cellular proliferation by stimulating the activity of aromatase with the consequent estrogen production, but also these estrogens are responsible for enhancing PGE2 synthesis by stimulating COX-2 activity. PGE2 also stimulates angiogenesis and is implicated in the peritoneal immunologic alterations observed in endometriosis. COX-2 inhibitors were and are used in a vast number of preclinical and clinical studies in different types of cancer. In studies conducted both in vitro and in vivo, we have demonstrated that the selective COX-2 inhibitor, celecoxib, was efficient in inhibiting experimental endometriosis. It is important to search for new horizons in endometriosis treatment. Prostaglandins and the enzymes in charge of their synthesis, COXs, represent an attractive target for developing new therapies that attack directly the molecules involved in the causes of this pathology.